2015
DOI: 10.1080/09064710.2015.1006670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress on biomass and ash composition of switchgrass (Panicum virgatum)

Abstract: This study was to evaluate the effects of salt stress on the biomass production and fuel characteristics of energy crop switchgrass in Northern China. A greenhouse-pot experiment was conducted to investigate the salt tolerance of the Blackwell, Cave-in-rock and Sunburst cultivars, using the dominant native grass Leymus chinensis as a reference. All three switchgrasses yielded a greater aboveground biomass per plant than Leymus under low-salt conditions (≤2 g NaCl kg −1 ). However, their biomass production decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
4
12
0
Order By: Relevance
“…In general, perennial grasses can perform well under EC values below 10 dS m −1 and soil pH below 8.5. In North China, Zhuo et al (2015), in a greenhouse pot experiment of switchgrass cultivars (Cave-in-Rock, Blackwell, and Sunburst), reported that tolerance to salts varied among the cultivars and were in this order: Cave-in-Rock > Blackwell > Sunburst. All cultivars performed well at £2 g NaCl kg −1 , but yields decreased at higher salt concentrations.…”
Section: Acidic and Saline Soilsmentioning
confidence: 99%
“…In general, perennial grasses can perform well under EC values below 10 dS m −1 and soil pH below 8.5. In North China, Zhuo et al (2015), in a greenhouse pot experiment of switchgrass cultivars (Cave-in-Rock, Blackwell, and Sunburst), reported that tolerance to salts varied among the cultivars and were in this order: Cave-in-Rock > Blackwell > Sunburst. All cultivars performed well at £2 g NaCl kg −1 , but yields decreased at higher salt concentrations.…”
Section: Acidic and Saline Soilsmentioning
confidence: 99%
“…For switchgrass (Panicum virgatum), reductions in aboveground and belowground biomass have been reported in response to salinity, but almost all the available information is based on germination and seedling studies [22]. There are, however, some long-term exposure studies with switchgrass that have highlighted high emergence rates and biomass production in both lowland and upland switchgrass types exposed to moderate to high salinity [23,24]. This suggests that switchgrass may be a good candidate for bioenergy production in marginal lands affected by salinity.…”
Section: Introductionmentioning
confidence: 99%
“…The content of ash in plant raw material of Panicum virgatum L. varieties in seed ripening phase, % Biomass properties such as ash composition can affect energy conversion processes such as direct combustion (Zhuo et al, 2015). Investigations of ash content showed that this sign was in a range from 3.04% (Panicum virgatum f. RR) to 5.27 (Panicum virgatum f. SL-1) %.…”
Section: Tablementioning
confidence: 99%